Projected Future Flooding Pattern of Wabash River in Indiana and Fountain Creek in Colorado: An Assessment Utilizing Bias-Corrected CMIP6 Climate Data - Swarupa Paudel; Neekita Joshi; Ajay Kalra (Forecasting, 2023)
Climate change is considered one of the biggest challenges around the globe as it has been causing alterations in hydrological extremes. Climate change and variability have an impact on future streamflow conditions, water quality, and ecological balance, which are further aggravated by anthropogenic activities such as changes in land use. This study intends to provide insight into potential changes in future streamflow conditions leading to changes in flooding patterns. Flooding is an inevitable, frequently occurring natural event that affects the environment and the socio-economic structure of its surroundings. This study evaluates the flooding pattern and inundation mapping of two different rivers, Wabash River in Indiana and Fountain Creek in Colorado, using the observed gage data and different climate models. The Coupled Model Intercomparison Project Phase 6 (CMIP6) streamflow data are considered for the future forecast of the flood. The cumulative distribution function transformation (CDF-t) method is used to correct bias in the CMIP6 streamflow data. The Generalized Extreme Value (L-Moment) method is used for the estimation of the frequency of flooding for 100-year and 500-year return periods. Civil GeoHECRAS is used for each flood event to map flood extent and examine flood patterns. The findings from this study show that there will be a rapid increase in flooding events even in small creeks soon in the upcoming years. This study seeks to assist floodplain managers in strategic planning to adopt state-of-the-art information and provide a sustainable strategy to regions with similar difficulties for floodplain management, to improve socioeconomic life, and to promote environmental sustainability.